Low-temperature co-sintering for fabrication of zirconia/ceria bi-layer electrolyte via tape casting using a Fe2O3 sintering aid. Issue 13 (October 2017) - Mehranjani, A.S.; Cumming, D.J.; Sinclair, D.C.; Rothman, R.H.
Abstracts: Bilayer electrolytes have potential in solid oxide cells to improve ionic conduction whilst blocking electronic conduction. GDC/YSZ bilayer electrolyte processing has proven problematic due to thermochemical instability at high sintering temperatures. We first match the shrinkage profile of the two bulk materials using a Fe2 O3 sintering additive. Additions of 5 mol% of Fe2 O3 in the GDC layer and 2 mol% of Fe2 O3 in the YSZ layer prevents delamination during co-sintering. The addition of Fe2 O3 promotes densification, enabling achievement of a dense bilayer at a reduced sintering temperature of 1300 °C; ∼150 °C below conventional sintering temperatures. Elemental analysis showed the compositional distribution curves across the bilayer interface to be asymmetric when Fe2 O3 is employed. The Fe2 O3 increases the total conductivity of the bilayer electrolyte by an order of magnitude; this is explained by the effect of Fe2 O3 on reducing the resistive solid solution interlayer at YSZ/GDC interface from ∼15 to ∼5 μm.